INTRODUKSI FORMULA RIZOBAKTERIA Bacillusthuringiensis pv. toumanoffi PADA TANAMAN KEDELAI UNTUK PENINGKATAN KETAHANAN TERHADAP PENYAKIT PUSTUL BAKTERI (Xanthomonas axonopodispvglycines) DI LAPANGAN - Julio Eiffelt Rossaffelt Rumbiak; Trimurti Habazar; Yulmira Yanti (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2018)
Bacillus thuringiensis srv.toumanoffi is an indigenous endophytic rizobacteria from healthy soybean rizosphere capable of controlling bacterial pustule disease (Xanthomonas axonopodispvglycines). Rhizobacteria needs to be formulated to remain effective in storage and application. The aimed of this research was to obtain a stable bacterial formula in controlling bacterial pustule disease in soybeans. This research was designed in factorial in a randomized group consisting of 13 treatments with 3 replications. The Treatment was a combination of carrier material (peat, tapioca and coconut water+1% palm oil) and storage time (0, 2, 4, and 6 weeks). Soybean seeds were introduced with each Bacillus thuringiensis srv. toumanoffi formula before planting. The results showed that the formula Bacillus thuringiensissrv. toumanofi was relatively stable in suppressing the incidence and severity of bacterial pustule disease in soybean leaf. The best formula for controlling bacterial pustules was Bacillus thuringiensis srv. toumanoffi in peat, coconut water + palm oil and tapioca each 2 weeks storage.